Date Palm Fiber-Reinforced Recycled Polymer Composites: Synthesis and Characterization - Ali, Malek; Al-Assaf, Anwar H.; Salah, Mohammad (Advances in polymer technology, 2022)
In this research study, Recycled Polymer (RP) composites are synthesized by using compression molding process, initial mixtures of RP and Date Palm Fibers (DPF) with four different lengths (e.g., 2.5, 5, 7.5, and 10 mm) and weight ratios (e.g., 5, 10, 15, and 20 wt%). The RP composites utilized in this study are polyethylene and polypropylene. The mixtures of RP and DPF are heated at 80°C and then poured into a priori prepared mold. The mold is designed to have three cavities for three specimens in order to characterize them through impact, creep, and tensile tests. The results showed that the hardness and impact increased with this process. In addition, an increase in the DPF up to 15 wt% was observed with a small increase in the DPF length. High creep resistance was also observed to be 10 mm with 20 wt% in the DPF specimens. The maximum strain was obtained in a 2.5 mm fiber length with 5% of DPF due to ductility of the plastic matrix. Moreover, with a small ratio of tough DPF, short fibers are unable to block or resist rapid plastic deformation in specimens. In fact, the DPF specimens of 10 mm length with 20 wt% exhibit a high tensile strength of 78 N/mm2 in comparison with other composite specimens. This is due to the length and content of fibers, which improve transferring action and microfailure modes.